Serum immunoglobulins in neonatal diarrhoeic calves evaluation by glutaraldehid coagulation test - İsmail Şen; Abdullah Başoğlu; Mahmut Ok; Fatih M. Birdane; Hasan Güzeibeklaş; Turan Civelek (Eurasian Journal of Veterinary Sciences)
The aim of (his study, in neonatal calves, to carry out the relationship between diarrhea and passive co-lostral transler and the safety ol GA test using SRID (Single Radial Immunodiffussion} lest for its determination In this study, healty 20 and diarrheic 30, totally 50 calves were used as a material. Serum immunglobulin levels were measured by GA test as semiquantitative and by SRID test as kantitative. In the some diarrheic calves IgG levels were 250-400 mg/dl and their serum incougulated in 30 minutes. In the meantime, IgG levels of olher diarrhoeic calves were 580-800 mg/dl and their serum semisolid (jelous) at between 12-28 minutes. In the healty calves, serum samples with IgG level of 2400-5800 mg/dl coagulated in 1-5 minutes and serum samples with IgG level of 1600 mg/ dl coagulated in 6 to 7 minutes. As a result, it could be said that diarrhea is connected with passive colostral transfer, and calves with negative and jelous GA test have failure of passive colostral transfer and calves with positive GA test have adequate passive colostral transfer.